On the difference between verbal and nonverbal behavior - Catania, A. Charles (1986)
Language theorists have often proposed lists of the defining properties of language. This account reviews some of these and offers as an alternative a three-item list consisting of instructional control, equivalence classes, and autoclitic processes.